DEVELOPMENT OF TOURISM IN THE INTERNET SPACE - Yaxshiyeva, Zulfizar (Журнал иностранных языков и лингвистики, 2021)
Following work is dedicated to one of the trends in the development of tourism, in particular, its functioning in the Internet space. The purpose of this article is to identify the features of the tourist vocabulary of the modern Uzbek language under the influence of the Internet language.